Cost of living crisis: a UK crisis with global implications - A call to action for paediatricians - Guddi Singh; Amaran Uthayakumar-Cumarasamy (BMJ Publishing Group, 2022)
The UK's 'cost of living crisis' (COLC) has thrown millions of families into poverty in 2022, delivering an intensifying economic shock that will likely eclipse the financial impact of the global coronavirus pandemic for children, families and communities alike. But what is the relevance for paediatricians? Written by doctors who spend considerable time confronting social problems from clinical, public health and advocacy perspectives, this article aims to untangle the COLC for those working in child health and seeks to stimulate a meaningful conversation about how we might reimagine paediatrics for life in the 21st century.Taking the current crisis as our point of departure, we argue that the UK's COLC can be best understood as a 'crisis of inequality', which has been created through social, economic and political processes that were not inevitable. The health impacts, then, are a matter of health equity and social justice. While the acuity of the crisis unfolding in the UK garners much attention, the implications are global with lessons for paediatricians everywhere. We propose that using a 'social lens' for understanding the true 'causes of the causes' of complex challenges such as COLC is essential for the 21st century paediatrician, as the consequences for child health is deep, wide-ranging and long-lasting. However, the current gap in knowledge, skills and infrastructure in this area leads to disempowerment in the profession.We end with this provocation: What, after all, does it mean to be a paediatrician in a time of economic crisis? We offer thoughts about how paediatrics might respond to social challenges, such as the COLC, acknowledging that organised and concerted action must be taken both inside and outside of health systems if we are to help bring about the changes that our patients and their surrounding communities urgently need.